2023
DOI: 10.1073/pnas.2208361120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of crowding on the diversity of expanding populations

Abstract: Crowding effects critically impact the self-organization of densely packed cellular assemblies, such as biofilms, solid tumors, and developing tissues. When cells grow and divide, they push each other apart, remodeling the structure and extent of the population’s range. Recent work has shown that crowding has a strong impact on the strength of natural selection. However, the impact of crowding on neutral processes, which controls the fate of new variants as long as they are rare, remains unclear. Here, we quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The ensuing back-and-forth of growth-induced jamming and unjamming can be readily observed, for instance, when yeast cells grow in partially confined microfluidic incubators 74 , 116 . Similar dynamic arrangements, with additional contact dynamics due to dynamic changes in cell shape, have been modelled and observed in growing tissues and tumours over longer timescales 110 , 117 , 118 .…”
Section: The Effects Of Being Discretementioning
confidence: 99%
See 2 more Smart Citations
“…The ensuing back-and-forth of growth-induced jamming and unjamming can be readily observed, for instance, when yeast cells grow in partially confined microfluidic incubators 74 , 116 . Similar dynamic arrangements, with additional contact dynamics due to dynamic changes in cell shape, have been modelled and observed in growing tissues and tumours over longer timescales 110 , 117 , 118 .…”
Section: The Effects Of Being Discretementioning
confidence: 99%
“…Whereas the macroscopic structure of proliferating active matter clearly reflects past growth (Fig. 1 ), it is an interesting general question whether and how the statistical properties of dense ensembles of self-replicating cells differ from the properties of disordered granular packings 116 , 125 , 126 . A topological study of 2D colonies of rod-shaped bacteria growing at a constant rate observed that, although +1/2 and –1/2 defects were both produced at the same rate, +1/2 defects tended to move to the periphery 127 , in contrast to the defect dynamics in non-growing active nematics.…”
Section: The Effects Of Being Discretementioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere, authors have noted that 'bubbles' of mutant cells trapped within the colony could be relevant if they remain viable and could re-grow following clearance of the surrounding wild-type (e.g. by antimicrobial treatment) [37,38].…”
Section: Methods 2: Sector In Expanding Coloniesmentioning
confidence: 99%
“…For instance, methods can now be applied to situations where final population sizes vary among experiments, where mutants grow differently than the wild type and where only a sub-sample of the culture is screened for mutants [22,24,27,28]. Moreover, methods have been developed to deal with specific ecological complications such as growth in colonies and biofilms or in the presence of killing agents [29][30][31]. More details about the major tools are provided in Supplementary Table S1.…”
Section: Introductionmentioning
confidence: 99%